HIGHER EDUCATION MARKET SEGMENTATION - Boris Marjanović; Marino Učeta (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The paper analyzes the issue of identification of market segments in the higher education market. Segmentation is an important tool in achieving competitive advantage especially in mature and highly competitive markets. The higher education market is highly competitive especially in recent times when borders are open and student mobility is extremely accessible and easy to achieve. The market is open and every foreign higher education institution is a serious competitor to the domestic ones in the Republic of Croatia. This research established the existence of seven specific market segments in the higher education market in Croatia based on one of the behavioral criteria, specifically on the benefit criterion. Based on the established factors, Croatian higher education institutions can adjust their own educational service with regard to the specifics of the targeted segments, which can give them an advantage over other competitors in the market.